Choline supplements: An update - Kansakar, Urna; Trimarco, Valentina; Mone, Pasquale; Varzideh, Fahimeh; Lombardi, Angela; Santulli, Gaetano (Frontiers in Endocrinology, 2023)
In this comprehensive review, we examine the main preclinical and clinical investigations assessing the effects of different forms of choline supplementation currently available, including choline alfoscerate (C8H20NO6P), also known as alpha-glycerophosphocholine (α-GPC, or GPC), choline bitartrate, lecithin, and citicoline, which are cholinergic compounds and precursors of acetylcholine. Extensively used as food supplements, they have been shown to represent an effective strategy for boosting memory and enhancing cognitive function.